Dioxidomolybdenum(VI) and -tungsten(VI) complexes with tetradentate amino bisphenolates as catalysts for epoxidation - Schachner JA; Mösch-Zanetti NC; Peuronen A; Lehtonen A (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Sixteen molybdenum and tungsten complexes with tripodal or linear tetradentate amino bisphenol ligands were studied as catalysts for the epoxidation of cis-cyclooctene, 1-octene, styrene, limonene and alpha-terpineol. These complexes can be divided into different categories upon key features, i.e. central metal (Mo versus W), side-arm donor (O versus N), hybridization of the N-donor (pyridine versus amine), ligand geometry (tripodal versus linear diamine) and sterical hindrance (Me versus tert-Bu substituents in the phenol part). All complexes can catalyse selectively the epoxidation of cis-cyclooctene by tert-butylhydroperoxide whereas the activities and selectivities towards other olefins (1-octene, styrene, limonene and cc-terpineol) show large differences. When H2O2 was used as an oxidant in the epoxidation of cis-cyclooctene, only two of eight Mo complexes and four of eight W complexes showed any activity. This study revealed no clear correlations between the Mo and W catalyst structures and their activities. (c) 2017 Elsevier Ltd. All rights reserved.